Werk at Play: Exploring the Creative Play of a Graduate Student Writer to Reimagine Graduate Writing in the Humanities - Michelle LaFrance; Jay Hardee (Journal of the Assembly for Expanded Perspectives on Learning, 2022)
This nontraditional essay poses the imaginative possibilities of fostering creative, intellectual play in graduate classes in the Humanities. Exploring the case study of a vlog produced by a student in a graduate seminar, the essay traces how the hybrid, multimodal writing—writing that meshes the digital conventions of creative and scholarly genres—in the course enabled this student to “reimagine” the purpose and stock moves of effective “scholarly” writing as the student blended voices, identities, and genres in his work. Creative play can be understood as an important pedagogical tool that allows graduate students to resist coercive and exclusionary processes of socialization, the co-authors argue. Such assignments encourage powerful interventions into traditional models of academic preparation, opening literacy landscapes of reimagined “world-building” and belonging.
Keywords: JAEPL